Testing of different material type photoelectric battery and photothermal batteries composed - Tursunov, M.N; Sabirov, X.; Abilfayziyev, Sh.N.; Yuldoshov, B.A. (Karagandy University of the name of acad. E.A. Buketov, 2022)
In the world, over the years, the use of hydrocarbon resources is decreasing, and their place is being replaced by ecologically clean alternative and renewable energy sources. Therefore, the world is paying a lot of attention to improved devices based on photoelectric batteries. Conducting targeted scientific research in this direction is one of the urgent issues of the present time. This article presents the results of comparing the electrical parameters of photovoltaic and photothermal batteries based on them in natural conditions. The experiments were carried out on three traditional photoelectric batteries with different materials and constructions, as well as photothermal batter ies made on their basis. All batteries are installed in a mobile structure, and two planes (reflectors) that reflect sunlight are installed along the long side of the device connecting the batteries. In the same conditions, the intensity of solar radiation is increased with the help of reflectors that return light to photoelectric and photothermal batteries. On the front surface of the photovoltaic batteries, a vertical (90°) fall of the sun's rays is provided. As a result, their electrical parameters changed to different values depending on the type of material and construction. Compared to traditional photoelectric batteries, photothermal batteries produced 1.3-1.4 times more electricity depending on the type of material. In the results of the experiment, data were obtained on the open circuit voltage, short circuit current and power of photoelectric and photothermal batteries in hot climate conditions. According to results, the high indicators in terms of electrical parameters are monocrystalline photoelectric and photothermal batteries based on them.
Keywords: monocrystal; polycrystal; photothermal; mobile device; heat collector; cellular polycarbonate; open circuit voltage; short circuit current